Implementation of video editing and making poster designs as internship activities at PT Ampu Studio - Rifa Alfazri; Argiyan Dwi Pritama (Universitas Amikom Purwokerto, 2023)
In the growing digital era, poster design and video editing have become two crucial aspects of visual communication. Poster design plays an important role in promoting events, products, or campaigns, while video editing allows for engaging content creation and reaching a wider audience. The use of visual media, such as videos and posters, has become an effective means of conveying messages and information. The creative approach in implementing these two media is the main focus because creativity plays a central role in producing attractive and effective visual works in communication. Challenges in facing this digital era include increasingly fierce competition, requiring unique and innovative creative approaches. The opportunities presented by digital technology are also important factors in creating more efficient and competitive designs and videos.